Cost-Benefit Analysis Case Study on Regulations to Lower the Level of Sulphur in Gasoline - Glenn Jenkins; Chun-Yan Kuo; Aygul Ozbafli (Queen's University, Department of Economics, 2007)
The Canadian Cost-Benefit Analysis Guide: Regulatory Proposals, sets out the general methodology and analytical steps to perform a cost-benefit analysis of proposed regulatory changes. To make the Guide operational, this case study has been prepared following the analytical approach recommended by the Guide. In 1994, the sulphur content of Canadian gasoline was found to be high and varied widely across the country. Scientists and health experts have found evidence that emissions of pollutants from vehicles cause considerable harm to the health of Canadians and to the environment. In order to derive the net economic benefits, we integrate the economic benefits with the economic costs for each of the alternative scenarios. In the cost-benefit analysis, all private costs must be measured in terms of their economic opportunity costs. The results indicate that reducing the sulphur in gasoline for any scenario under consideration would generate substantial net health benefits or well-being for Canadians as a whole. Estimates of the net present value (at an eight percent discount rate) range from 1,809 million to 2,663 million.
Keywords: D61; Q52; Q53; 330; Gasoline; Sulphur; Cost-Benefit; Environment; Umweltpolitik; Umweltbelastung; Schwefel; Kraftstoff; Kosten-Nutzen-Analyse; Kanada